1998
DOI: 10.1590/1807-1929/agriambi.v2n3p329-334
|View full text |Cite
|
Sign up to set email alerts
|

Determinação Do Teor De Umidade De Sementes De Trigo Por Meio Da Medição Simultânea De Dois Parâmetros Dielétricos Em Uma Única Freqüência

Abstract: RESUMOEm trabalhos anteriores, os autores avaliaram diversas metodologias que tinham como princípio básico a medição de parâmetros dielétricos para estimar a quantidade relativa de água presente em amostras de produtos granulares e que foram adaptadas para o cálculo do teor de umidade de sementes de trigo. Avaliou-se tanto a medição simultânea de um (ε') ou dois (ε' e ε") parâmetros dielétricos em duas freqüências de oscilação, quanto a medição desses dois parâmetros em uma única freqüência. Estas são as duas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Comparison of the results obtained in the present work with those reported by Berbert & Stenning (1998) revealed that the Meyer and Schilz function performs slightly better in terms of the indirect estimation of moisture content of wheat seeds than that of common bean seeds. The use of the function [(ε'-1)/ε"] 1MHz allowed density-independent estimation of the moisture content of wheat seeds with a standard error of estimate and maximum error of 0.3 and 0.7, respectively.…”
Section: ( ' -1)/ "]supporting
confidence: 67%
See 1 more Smart Citation
“…Comparison of the results obtained in the present work with those reported by Berbert & Stenning (1998) revealed that the Meyer and Schilz function performs slightly better in terms of the indirect estimation of moisture content of wheat seeds than that of common bean seeds. The use of the function [(ε'-1)/ε"] 1MHz allowed density-independent estimation of the moisture content of wheat seeds with a standard error of estimate and maximum error of 0.3 and 0.7, respectively.…”
Section: ( ' -1)/ "]supporting
confidence: 67%
“…Meyer & Schilz (1980) reported that the uniqueness of the ratio [(ε'-1)/ε"] as a function of moisture of granular materials was only attained for values of frequency above approximately 10 GHz. Nonetheless, Berbert & Stenning (1998) studying the dielectric properties of wheat seeds at radiofrequencies observed that an uniqueness of the function [(ε' -1)/ ε"] was achieved over much lower frequencies. In the present work, analysis of the experimental results revealed that the function is not unique at any frequency from 75 kHz to 5 MHz ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%